Peran Digitalitasi Ekonomi Untuk Membentuk Kemandirian Ekonomi Pondok Pesantren - Abdulloh Majid; Heni Noviarita; Erike Anggraeni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Economic developments have made various economic sectors enter the digital era. Various economic sectors, both on a macro and micro scale, are starting to use digital technology in carrying out their business activities. This is done in order to develop its business activities and survive in an increasingly complex market. Darul Muttaqin Al-Islami Islamic Boarding School is an Islamic-based educational institution which has a business unit and starts using digital technology. The purpose of this study is to look at the role of digitalization in the economic independence of Islamic boarding schools. The research method used is quantitative with research field research. The sampling method uses purposive sampling or sampling with criteria. The number of samples in this study was 100 samples with data collection methods in the form of questionnaires. The results of the study show that digitalization has an effect on economic independence at the Darul Muttaqin Al-Islami Islamic boarding school. This is evidenced by the value of tcount > ttable (5.874 > 1.29007) and the effect of economic digitalization of 37.9% on the economic independence of Islamic boarding schools. This situation shows that the importance of increasing digitalization in the Darul Muttaqin Al-Islami Islamic Boarding School given its positive benefits.